Pengaruh Konsumsi Buah Pisang Ambon Dan Diit Rendah Garam Terhadap Penurunan Tekanan Darah Pada Penderita Hipertensi Usia Lanjut Di Desa Babakan Karet Kecamatan Cianjur Kabupaten Cianjur Tahun 2023 - Milah Awalia; Emi Yuliza; Weslei Daeli (Pusat riset dan Inovasi Nasional, 2024)
Hypertension or high blood pressure is a condition where the blood pressure in the arteries is too high, where the blood pressure rises, namely systolic blood pressure ≥140 mmHg and/or diastolic blood pressure ≥90 mmHg. To overcome this problem, non-pharmacological treatment efforts are needed to reduce blood pressure, namely by consuming Ambon bananas and a low-salt diet. To determine the effect of consuming Ambon bananas and a low-salt diet on reducing blood pressure in elderly hypertensive sufferers in Babakan Karet Village, Cianjur District, Cianjur Regency. The research design uses a pre-experimental method with one group pretest-posttest, with purposive sampling and using dependent T-Test data analysis. The research population who suffered from hypertension was 30 people, the sample size was 17 respondents. The dependent T-test showed a significance value of <.001 (<0.05), meaning that there was an effect of consuming Ambon bananas and a low-salt diet on reducing blood pressure in elderly hypertensive sufferers in Babakan Karet Village, Cianjur District, Cianjur Regency. There is a therapeutic effect of consuming Ambon bananas and a low-salt diet on reducing blood pressure in elderly hypertensive sufferers